The Influence of a Learning Model with Scientific Approach on Soccer Skills - Hendrayana, Yudy; Widyawan, Dena (ASPENSI in Bandung, Indonesia, 2016)
ABSTRACT: Physical education teaching and learning should be holistic, accommodating the physical, spiritual, and social aspects. Education through physical activities is expected to provide students with real learning experience. The aim of this research is to analyze the influences of problem-based learning on soccer skills, which are expected to contribute positively to the meeting of the objectives of Curriculum 2013 in Indonesia. The research adopted experimental method with non-equivalent group pre-test post-test design. It was conducted at the SMPN (Public Junior High School) 2 Rangkasbitung, Lebak, Banten, Indonesia, with the sample consisted of 60 students, in which 30 students for the experimental and control groups, respectively. The research was carried out for seven weeks, with each week consisting of two meetings. GPAI (Game Performance Assessment Instrument) was used as the instrument to measure soccer skills. Data were analyzed with t-test, aided by SPSS (Statistical Package for Social Sciences) version 18. The findings of this research are: with problem-based learning model, studentsâ soccer skills increased significantly, as reflected from their post-test scores which were greater than their pre-test scores; with direct instructional model, studentsâ soccer skills increased significantly, as indicated by the increase in their post-test scores compared to their pre-test scores; and problem-based learning model influenced studentsâ soccer skills more significantly than direct instructional model.KEY WORD: Problem-Based Learning Model; Soccer Skills; Curriculum 2013; Direct Instructional Model; Scientific Approach.Â RESUME: âPengaruh Model Pembelajaran melalui Pendekatan Saintifik terhadap KeterampilanÂ Bermain Sepakbolaâ. Pengajaran dan pembelajaran pendidikan jasmani harus holistik, menampung aspek fisik, spiritual, dan sosial. Pendidikan melalui gerak fisik diharapkan dapat memberikan pengalaman belajar nyata kepada siswa. Tujuan kajian ini adalah untuk menganalisis pengaruh model pembelajaran berbasis masalah terhadap keterampilan bermain sepak bola, yang diharapkan memberikan manfaat positif terhadap pencapaian tujuan Kurikulum 2013 di Indonesia. Metode penelitian yang digunakan untuk mengungkapkan permasalahan tersebut adalah menggunakan metode eksperimen, dengan desain ânon-equivalent groups pre-test post-testâ atau kelompok tidak setara dengan pra dan pasca tes. Penelitian ini dilaksanakan di SMPN (Sekolah Menengah Pertama Negeri) 2 Rangkasbitung, Lebak, Banten, Indonesia, dengan mengambil sampel pada penelitian ini, yaitu 60 siswa yang terdiri dari 30 siswa pada kelompok eksperimen dan 30 siswa pada kelompok kontrol. Penelitian dilakukan selama 7 minggu, dengan 2 kali pertemuan setiap minggunya. Instrumen yang digunakan adalah GPAI (Game Performance Assessment Instrument atau Instrumen Penilaian Unjuk Permainan) untuk mengukur keterampilan bermain sepak bola. Teknik analisis data menggunakan uji-t, melalui SPSS (Statistical Package for Social Sciences) versi 18. Hasil penelitian menunjukan bahwa terdapat peningkatan yang signifikan keterampilan bermain sepak bola dari skor pra-tes ke pasca-tes dengan menggunakan model pembelajaran berbasis masalah; terdapat peningkatan yang signifikan keterampilan bermain sepak bola dari skor pra-tes ke pasca-tes dengan menggunakan model pengajaran langsung; serta model pembelajaran berbasis masalah lebih baik bila dibandingkan dengan model pembelajaran langsung terhadap keterampilan bermain sepak bola.KATA KUNCI: Model Pembelajaran Berbasis Masalah; Keterampilan Bermain Sepakbola; Kurikulum 2013; Model Pembelajaran Langsung; Pendekatan Saintifik.Â Â About the Authors: Dr. Yudy Hendrayana is a Senior Lecturer at the FPOK UPI (Faculty of Sports and Health Education, Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia. Dena Widyawan is a Lecturer of Sports Education at the STKIP (College of Education and Teacher Training) Situs in Banten, Indonesia. The authors are able to be contacted via their e-mails at: yudy@upi.edu and dena_widyawan@yahoo.comHow to cite this article? Hendrayana, Yudy & Dena Widyawan. (2016). âThe Influence of a Learning Model with Scientific Approach on Soccer Skillsâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.9(2) November, pp.325-334. Bandung, Indonesia: Minda Masagi Press and UPI Bandung, ISSN 1979-0112. Chronicle of the article: Accepted (April 15, 2016); Revised (August 17, 2016); and Published (November 20, 2016).